Regional economic planning and development for the Caribbean : the management imperative - Rainford, Roderick G. (UWI. Management Studies Department St AugustineTT, 1987)
Discusses the social, political and institutional environment for economic planning at the regional level and the limitation imposed by that environment upon planning. Identifies various regional programmes and projects which have been formulated viz. the Regional Energy Action Plan; the CARICOM Industrial Programming Scheme; the New Marketing Arrangement for Primary Agricultural Products and Livestock. Considers 7 management imperatives that are important to regional economic planning.